Nailing the tobacco coffin - Abd Razak, Dzulkifli (2004)
If there ever was doubt about the Government's commitment to cut down smoking, it should be laid to rest now. The 2005 Budget has hammered the last few nails into the tobacco coffin; an increase of about 40 per cent in excise duties. It pushed the price per 1,000 cigarettes from RM58 to RM81, and price of a pack of 20 sticks by more than RM1. IF this is not convincing, a few days later the Prime Minister again reminded Malaysians not to smoke, when launching the National Fitness Council.